2021
DOI: 10.1002/gcc.22997
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent NF1 gene variants and their genotype/phenotype correlations in patients with Neurofibromatosis type I

Abstract: Neurofibromatosis type I, a genetic condition due to pathogenic variants in the NF1 gene, is burdened by a high rate of complications, including neoplasms, which increase morbidity and mortality for the disease. We retrospectively re-evaluated the NF1 gene variants found in the period 2000-2019 and we studied for genotype/ phenotype correlations of disease complications and neoplasms 34 variants, which were shared by at least two unrelated families (range 2-11) for a total 141 of probands and 21 relatives affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…Variants in these protein domains are reported to affect the protein activity, leading to loss of function of the neurofibromin protein due to haploinsufficiency ( Bergoug et al, 2020 ; Zhang et al, 2021 ). The distribution of the variants in the NF1 gene protein domains is similar to the one observed in the literature where distribution of various pathogenic variant types throughout the gene with no obvious hotspot region ( Friedman, 1993b ; Abdel-Aziz et al, 2021 ; Legius et al, 2021 ; Riva et al, 2022 ). Missense variants were observed to cluster in the CSRD domain ( Figure 1 ) with no truncating variant observed, however the sample size in the current study is too small to make significant discussion on these.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Variants in these protein domains are reported to affect the protein activity, leading to loss of function of the neurofibromin protein due to haploinsufficiency ( Bergoug et al, 2020 ; Zhang et al, 2021 ). The distribution of the variants in the NF1 gene protein domains is similar to the one observed in the literature where distribution of various pathogenic variant types throughout the gene with no obvious hotspot region ( Friedman, 1993b ; Abdel-Aziz et al, 2021 ; Legius et al, 2021 ; Riva et al, 2022 ). Missense variants were observed to cluster in the CSRD domain ( Figure 1 ) with no truncating variant observed, however the sample size in the current study is too small to make significant discussion on these.…”
Section: Discussionsupporting
confidence: 83%
“…The high frequency of truncating variants compared to the missense variants was not unique to the present study. In a study by Riva et al, 2022 that reviewed NF1 patient records in Parma hospital in Italy, out of 34 variants identified, 67.6% (23) were frameshift and nonsense compared to one missense variant ( Riva et al, 2022 ). Although there are no significant differences in phenotype severity reported between truncating and missense NF1 variants in the literature as well as the current cohort, a study on NF1 missense variants ( Koczkowska et al, 2020 ) showed that some patients with these variants exhibited some Noonan syndrome phenotypes such as pulmonic stenosis, cardiovascular abnormalities, short stature and macrocephaly.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, more than 3000 different genetic variants in the NF1 gene have been reported, and most of them lead to loss of expression or synthesis of non-functional neurofibromin [78]. This increase in the amount of genetic data has led to numerous studies aimed at NF1 genotype-phenotype correlation [79][80][81][82][83]. Some of these studies reported agedependent manifestations of some cancers like optic pathway gliomas that are associated with younger pediatric NF1 patients [84].…”
Section: Nf1 Genementioning
confidence: 99%
“…NF1 is characterized by loss of the Nf1 gene which produces neurofibromin, a negative regulator of Ras-GTP signaling that modulates cell growth [22][23][24]. There are mutations in both Nf1 alleles in neurofibromas and neurofibroma SCs [11,[25][26][27][28]. Complete Nf1 loss of function in SCs correlates with neurofibroma formation.…”
Section: Introductionmentioning
confidence: 99%